Pressure drop analysis of 1.6L car air intake system - Mohamad Safwan, Ahmad Lothfy (2009)
Today, air intake system and filter play major role in getting good quality air into automobile engine. The intake system has improves the combustion efficiency and also reduces air pollution. This paper focuses on the pressure drop analysis of 1.6L car air intake system. The thesis describes the CFD analysis techniques to predict the pressure drop and identify the critical locations of the components. The air intake system is work as to supply the engine with clean air and correct amount for the required air to burn in the manifold chamber. This research is to analyze the model and pressure drop of Proton Waja intake system. The thesis describes the CFD analysis techniques to predict the pressure drop and identify the critical locations of the components. 3D viscous CFD analysis will carry out for an existing model to understand the flow behavior through the intake system, air filter geometry and filter media. Results obtain from CFD analysis of the existing model show good correlation with experimental data. Based on existing model CFD results, it can show the airflow in the intake system and the pressure drop will see by pressure visualization. The time and cost are reducing by using 3D CFD analysis for air intake system in automobile industry.